Educational challenges in nomadic pastoralist regions: Examining factors affecting academic performance in secondary schools in Samburu County - Lanyasunya, Ropilo (Editon Consortium Journal of Arts, Humanities and Social Studies, 2024)
The purpose of this study was to investigate the factors influencing students' academic performance in public secondary schools within Samburu County. The study sought to identify key factors contributing to the consistently low performance of students in the Kenya Certificate of Secondary Education (KCSE) exams in this region. The study used a descriptive survey design, employing structured questionnaires to collect data from Form IV school leavers and secondary school principals in Samburu County. The study examined environmental, school-related, family-related, and student-related factors affecting academic performance. Data was analysed using descriptive statistics, including mean, frequencies, and p-values. The study found that environmental factors, such as drought and insecurity, significantly impacted students' academic performance. In addition, inadequate learning resources and the absence of academic performance policies in schools were major school-related challenges. Family-related factors, especially the educational level of guardians, also played a crucial role. Student-related factors, such as school attendance, study time input, and lack of post-secondary goals, were identified as core contributors to poor performance. The study concluded that multiple factors, both external and internal to the school environment, contribute to the low academic performance of students in Samburu County. The study recommends a multi-dimensional approach to address these challenges, including improving financial support for students, enhancing learning resources in schools, motivating students through role models, and promoting flexible education delivery models. Additionally, community development initiatives aimed at improving parents' economic capacities are crucial to supporting students' education.